Common morbidities and felt needs of salt pan workers in a coastal area of Tamil Nadu, India - Vasudevan, Jyothi; Vaithiyalingam, Saravanan; Anandan, Velavan; Mishra, Amit Kumar; Purty, Anil J. (International Journal of Research in Medical Sciences, 2019)
Background: The occupational hazards faced by salt pan workers during their occupation are myriad, a fact compounded by the lack of basic amenities at their workplace and lack of awareness regarding usage of personal protection equipment. Methods: This cross-sectional study was carried out among fifty-six salt pan workers in Marakkanam, Tamil Nadu to assess their common health problems and a qualitative component was added to assess their felt needs in work place and daily living. Data was collected using pre-designed data collection sheet for assessing the common morbidities. For the qualitative aspect of the study, in-depth interviews were conducted among twenty workers based on convenient sampling, using open ended questions. Data was collected after obtaining informed consent and steps were taken to ensure confidentiality at all stages. Results: The most common health problem of the workers in present study area included dental caries (41.7%), skin conditions (38.1%) musculoskeletal problems (36.7%) and anemia (35.1%) being other significant health problems. The qualitative aspect of the study revealed that the felt needs were improvement of their working conditions and more social support from the Government and the employers. There was very little awareness among the workers regarding use of PPE and none of them used any form of PPE. Conclusions: Salt pan workers had dental problems, dermatological problems and musculoskeletal problems as most common morbidities among them. Harsh working conditions, financial insecurity etc. are some of their work-related problems. Provision of housing facility and financial assistance during off- season by the government, basic amenities at the work place, paid leave in case of injuries, and insurance schemes for them by employer are their main felt needs. They also had no awareness regarding usage of personal protective equipment at the work place.